A Stakeholder–Human Capital Perspective on the Link between Social Performance and Executive Compensation. Issue 1 (January 2014) - Madsen, Peter M.; Bingham, John B.
ABSTRACT: The link between firm corporate social performance (CSP) and executive compensation could be driven by a sorting effect (a firm's CSP is related to the initial levels of compensation of newly hired executives), or by an incentive effect (incumbent executives are rewarded for past firm CSP). Existing empirical work focuses exclusively on the incentive effect. In contrast, in this paper we explore the sorting effect of firm CSP on the initial compensation of newly hired executives. In doing so, we develop a novel theoretical approach based on an integration of stakeholder theory and human capital theory, suggesting a positive association between the initial compensation of executives and firm CSP strengths and concerns. It also suggests that the strength of this relationship varies between different executive roles (as a function of stakeholder-management responsibilities). We find support for this theoretical framework in a large sample of newly-hired executives employed by Standard & Poor 1500 firms.